Desenvolvimento de um método de análise classificatória de concepções de produto considerando diretrizes de mantenabilidade na etapa do projeto conceitual - Sulevis, Marcos (2015)
Currently, the automotive industry focused on heavy vehicles production, aim at offering high added value products for customers seeking a vehicle with a high operational availability and the ability to carry out maintenance in a planned, quick and correct approach. As maintenance is an action performed in a finished product, for it to be conducted with high quality, requirements must be addressed in the PDP stage. Based on the need to explore new advantages in the market, from the sales of the product itself to the aftermarket support, this thesis aims at presenting the development of a systematic that engage CAD tools, analysis tool for disassemble routes of mechanical assemblies and maintenance key rules, to produce a classification analysis that assists the service engineer along with the project team in the evaluation and selection, during the PDP, of concepts that best support maintainability guidelines. From a literature review, were explored information available on the PDP, studies related to components removal routes, maintainability requirements and multi criteria decision making tool usage. In this way, it was structured the method and process for the development of classification analysis of product proposals considering maintainability guidelines during the conceptual design stage. From the information collected from literature and field regarding the maintenance over the years, the assumptions that the method should meet were established. In the next step, the method was submitted to evaluation, by its application in an experiment conducted in a controlled environment. In this case, three pre-defined alternatives were selected and submitted to the method. Preliminary results indicate that the approach is satisfactory to assess conceptual alternatives based on maintainability criteria. Working maintainability systematically in the early stages of design enhances the product's chances of success. Thus, this tool can contribute in the aftermarket profits maximization, product availability increasing and maintenance cost reduction, due to the definition of differentiated products with added values.